Analyzing the Archiving Management Performance in the Department of Public Works and Spatial Planning - Pananrangi, Andi Rasyid; Hamka, Husain; Ismail, Imran; Hamid, Wahyuddin; Nurkaidah, Nurkaidah; Sahibuddin, Annamirah (Interdisciplinary Social Studies, 2023)
Background: In the process of presenting information so that leaders can make decisions and plan policies, there must be good systems and work procedures in the archives sector. An institution, be it a state or private institution, will not be able to provide good, complete and accurate information data, if the institution does not have good and regular archive management. Aim: Unveiling and analyzing the performance of archival management services of the Polewali Mandar’s District Department of Public Works and Spatial Planning Office and the obstacles encountered in optimizing service performance carried out by the archives section of the Polewali Mandar’s Department of Public Works and Spatial Planning Office. Method: This study used a qualitative descriptive approach. Data collection techniques were observation at the Polewali Mandar’s Department of Public Works and Spatial Planning, interviews with staff at the department, and documentation (Online and offline). Data analysis was carried out through data reduction, data display, conclusion drawing, and data verification. Findings: The human resources are still very lacking, and understanding and knowledge about archive management is still very minimal, shrinkage  of an archive in the office has never been done because of the lack of knowledge of employees in managing archives, there are cultural factors of bad habits that cause the absence of responsibility and discipline that causes a deterioration in employee performance. This factor is a bad example for other employees so that the sustainability of poor performance is inevitable and has an impact on employee work results.